Building the canon through the classics : imitation and variation in Renaissance Italy (1350-1550) - Morra, Eloisa, 1988- (Metaforms, 2019)
Building the Canon through the Classics. Imitation and Variation in Renaissance Italy (1350-1580) provides a comprehensive reappraisal of the construction of a literary canon in Renaissance Italy by exploring the multiple reuses of classical authorities. The volume reshapes current debate on the notion of canon by intertwining two perspectives: analyzing when and in what form a canon emerged, and determining the ways in which an ancient literary canon interacts with the urge to bestow a similar authority on some later and contemporaneous authors. Each chapter makes an original contribution to its selected topic, but the collective strength of the volume relies on its simultaneous appeal to readers in Italian Studies, intellectual history, comparative studies and classical reception studies.